MANFAAT SIM DALAM PENGAMBILAN KEPUTUASAN PADA SUATU PERUSAHAAN - Elmiano Artanto Epot Erong; Hwihanus Hwihanus (Pusat Riset dan Inovasi Nasional, 2023)
The existence of this system in the company provides great benefits for the company, especially in relation to decision making by the management of the party concerned. It is said so because this management information system presents data that is directly related to the company so that everything that will be carried out can be considered based on the data provided by this system. That way, in making decisions, the possibility for errors to occur is very small so that it can reduce the company's operating costs to a minimum.